2021
DOI: 10.1155/2021/7577349
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress of Crop Disease Image Recognition Based on Wireless Network Communication and Deep Learning

Abstract: The traditional digital image processing technology has its limitations. It requires manual design features, which consumes manpower and material resources, and identifies crops with a single type, and the results are bad. Therefore, to find an efficient and fast real-time disease image recognition method is very meaningful. Deep learning is a machine learning algorithm that can automatically learn representative features to achieve better results in areas of image recognition. Therefore, the purpose of this p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…By comparing the model training results of the pre- and post-enhanced datasets, a large amount of data is beneficial for optimizing model performance. In the future, with the application of various image recognition technologies in the field, more types and quantities of corn leaf disease data images will be collected [ 46 ], which can increase the types of corn leaf disease recognition, further improve the recognition accuracy and performance of the model, and enhance the robustness and generalization ability of the model [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…By comparing the model training results of the pre- and post-enhanced datasets, a large amount of data is beneficial for optimizing model performance. In the future, with the application of various image recognition technologies in the field, more types and quantities of corn leaf disease data images will be collected [ 46 ], which can increase the types of corn leaf disease recognition, further improve the recognition accuracy and performance of the model, and enhance the robustness and generalization ability of the model [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, disease spot recognition is still affected by various factors in field tests. [44][45][46] Light conditions are a frequently discussed factor. If the light intensity is too strong or too weak, the recognition accuracy of the model may decrease.…”
Section: Discussionmentioning
confidence: 99%
“…This showed that disease information has high real‐time recognition accuracy in the complex field environment, and laid the foundation for the function of real‐time disease spot recognition to guide the VA in this study. However, disease spot recognition is still affected by various factors in field tests 44–46 . Light conditions are a frequently discussed factor.…”
Section: Discussionmentioning
confidence: 99%
“…Faced with hundreds of millions of Chinese farming households, having only approximately 550,000 Chinese national agricultural technology extension agencies are far from sufficient ( Zhang et al., 2016 ). Furthermore, (i) a large age gap among agricultural technicians, (ii) a lack of pest-recognition staff in each county-level plant protection station, and (iii) differing field experiences are causing a low cover density of experts specializing in pest identification and a lack of unified pest-identification criteria, thereby leading to the blind application of pesticides and serious environmental pollution ( Yu, 2021 ).…”
Section: Introductionmentioning
confidence: 99%